Development of nano-mechanical testing sytem for effective assessment of mechanical properties of perpendicular recording magnetic thin films - Zhou, Quan. (2009)
A magnetic recording disk coated with multilayer thin films is one of the most important components in a hard disk. Failure due to nano-scale scratches on the sputtered thin film layer has imposed a great concern on reliability of hard disk. This is due to the inherent weakness of the perpendicular aligned HCP crystal structure against scratch induced shear stress. The importance of establishing a measurement system to assess the thin film’s resistance against scratches and understand the factors for improvement in the design phase has been realized by the industry. This paper is targeted to provide a measurement solution for media manufacturing industry. Background introduction and theoretical review of available hardness testing methodology is covered in the first part of the paper. An introduction on media manufacturing process with focusing on sputtering technology is the covered to give basic understanding on the nature of the measured sample. Nano-mechanical properties like hardness, contact stiffness, reduced modulus, contact depth and scratch depth are measured on seven samples with different thin film design through Hysitron indenter and atomic force microscope. It is found that scratch depth from nano-scratch testing gives best resolution to differentiate the samples mechanical property the best correlation to the failure rate. A detailed test methodology with focus on measuring scratch depth of the sputtered thin film is then developed. Control of measurement error is also discussed in great details, a proper control on indentation tip, AFM tip, reference disks and AFM images quality can help achieve less than 0.1 nm measurement variation. Factors and its effect on scratch depth performance of sputtered thin film are also discussed in the last part of this paper.